New combination of drugs to combat Escherichia coli DSM1103 QCDSM by reducing antibiotic ciprofloxacin standard dose using response surface methodology - Jawaher I. AlAhadeb (Elsevier, 2021)
Background: Microbial diseases are emerged as a concern for the global health and are responsible for increased mortality among different age groups. It is therefore essential to control the microbial population with novel antimicrobial agents. Antibiotic-phytochemicals mixtures are used for improving the antibacterial efficiency against bacterial pathogens to decrease their microbial resistance development. This study compared the inhibitory potentials of ciprofloxacin antibiotic and phytochemical mixtures of Syzygium aromaticum (clove), Allium sativum (garlic) and Cinnamomum verum (cinnamon) against Escherichia coli DSM1103 QCDSM using Minimal inhibitory concentrations (MICs) and Bactericidal inhibitory concentrations (MBCs) methods. Objective: Inhibitory activity of ciprofloxacin and three oil plant extracts of the selected plants (clove, garlic, cinnamon) were tested against E. coli DSM1103 QCDSM using well diffusion method on Muller-Hinton agar plates by studying MIC and MBC tests. The software "Design Expert® 12" Stat-Ease was used to analyze the experimental mixture design. Results: A mixture design of twenty mixture combination runs using different concentration levels of ciprofloxacin and the three oil plants extracts were performed against E. coli DSM1103 QCDSM growth. Results revealed that the standard recommended ciprofloxacin dose 5 μg/100 ml may be replaced by the oil extracts of S. aromaticum 4.75 % (v/v), A. sativum 5.0% (v/v), C. verum 5.0%(v/v) and ciprofloxacin 0.25% (w/v) as alternative drugs. Conclusion: The proposed mixture containing Syzygium aromaticum (clove), Allium sativum (garlic) and Cinnamomum verum (cinnamon) was found to be an effective antimicrobial agent and may signifies the role of traditional knowledge in drug discovery.